PENGARUH MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR SEJARAH SISWA KELAS XI di MAN INSAN CENDEKIA SIAK - Hermawati, Ulan; Bunari, Bunari; Asril, Asril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the suboptimal cognitive learning outcomes of students in history learning. This is indicated by the low level of student participation during the learning process, such as the lack of involvement in asking questions, engaging in discussions, and expressing opinions, resulting in less optimal understanding of the material. This condition shows the need for the implementation of a learning model that can increase students’ active involvement. Therefore, this study aims to determine the implementation of the Numbered Heads Together (NHT) learning model in improving students’ history learning outcomes, to examine the effect of the NHT learning model on students’ learning outcomes, and to identify the extent of its influence in improving the learning outcomes of eleventh-grade students at MAN Insan Cendekia Siak. The research method used is a Quasi-Experimental Design with a Nonequivalent Control Group Design. The subjects of this study consisted of two classes: an experimental class of 24 students taught using the NHT learning model and a control class of 25 students taught using conventional methods. Data collection techniques were conducted through learning outcome tests in the form of pretests and posttests. Data analysis included validity, reliability, normality, and homogeneity tests, hypothesis testing using the t-test, and effectiveness testing using N-Gain. The results showed an improvement in students’ cognitive learning out comes after the implementation of the NHT learning model, with an N-Gain value of 0.64, which falls into the moderate category. Thus, it can be concluded that the Numbered Heads Together (NHT) learning model is quite effective in improving students’ history learning outcomes.